Fortini’s Literary Debt to Manzoni and Leopardi - Peterson, Thomas E. (L'ospite ingrato, 2023)
From his earliest publications until his final works, Franco Fortini was inspired by the models of Manzoni and Leopardi. Drawing on Manzoni’s philosophical-historical essays, narrative works and Inni sacri, Fortini revitalized our understanding of the Milanese poet, whose sublime vocabulary penetrated into Fortini’s late verse. In a contrasting but complementary way, Fortini embraced Leopardi, especially the poet of the Canti, elevating our understanding of the poet’s final, Neapolitan period. Assisted by studies of Lenzini, Diaco, Bonavita and others, the essay establishes the intellectual and poetic counterpoint represented in Fortini’s thought and poetry by these two giants of the Ottocento.